Sustainable withdrawal rates during retirement and the risks of financial ruins - Alles, Lakshman (Financial Service Institute of Australia, 2012)
The importance of sustainable spending rates by retirees has been underscored by rapid population ageing and the lacklustre performance of markets and pension funds in the post- GFC period. This suggests that financial planners and advisors should pay more attention to the estimation of risk in retirement finance modelling in their analyses and advice to clients. This paper provides some useful guidance on the application of two available techniques in this regard.